مولانا محمد یعقوب شرودیؒ اور ان کی تفسیر "کشف القرآن "کاتحقیقی وتعارفی جائزہ: Molana Muhammad Yaqoob Sherodi & his Tafseer, Kashf ul Quran, Analytical judicial Study - Siddiqui, Dr. Riaz Ahmed; Bano , Dr. Haseen (Journal of Quranic and Social Studies, 2022)
The Holy Quran is the basic Islamic divine book and a complete guide for all field of life. For better explanation of the Quran, Mufassireen and other Muslim Scholars have been engaged in writing Tafasir & books on its explanation and interpretations. Thus, molana Muhammad yaqoob is an Islamic Scholar, from Balochistan. In Islamic Studies, his interest is in Tafsir kashaf ul Quran and Hadith, specifically in Tafsir of The Holy Quran in Birahvi & Urdu languages He has authored many books in Arabic, Urdu & Birahvi languages on Tafsir, Fiqh and various other toipcs. Out of which some books have been published till now. Besides this, he has supervised many research scholars who worked on Tafsir projects. Islamic scholarship and authorship and contribution in the field of Quran and its sciences, are of paramount importance but unfortunately very little number of people from academia know about it.This paper presents a scholarly and analytical study of his contributions in Quranic Studies for the information, easy access and facilitation of research scholars in Islamic Studies.